Kemampuan Mahasiswa dalam Memilih Material pada Pembuatan Karya Teknologi - Tiwan Tiwan (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectivesof this study were to analyze the approaches applied by the studentstodetermine the type of materials, to examine the type of materials widely used by the students, and to assess the students’ accuracy in determining the type of materialsto produce technological works. This study was categorised into ex post facto study conducted at the Department of Mechanical Engineering Education, Faculty of Engineering, YSU. The samples were 139 students with39 units of machines. The data was obtained using documentation by examining the reports and the surveysof the developed technological works. The data was analysed descriptively. The results showed the students havethe ability to consider the criteria of materials selection based on materials science, including strength, usage, fabrication, availability and prices. The type of materials widely used is metal as follows: carbon steel, alloy steel, cast iron, stainlesssteel, aluminum and copper. The carbon steel is the most widely used material utilized by 62% of the students.There was36%of the components developed usinginaaccurately selected materials.